On Creating Viable Work Experience Programs Design and Implementation. Occasional Paper #3 - Hamilton, Mary Agnes; State Univ. of New York, Ithaca. Coll. of Human Ecology at Cornell Univ.; Youthwork, Inc., Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
As part of research on 48 programs funded through the Youth Employment and Demonstration Projects Act (YEDPA) of 1977, this study addresses two issues behind the creation of viable work experience programs: design and implementation. The purpose of the study is to help those responsible for organizing youth employment programs to identify points in program design and implementation whereby the quality of the educational experience that participants will have can be increased. Five work experience programs provided written materials, observations, and interviews used for case studies in this report. The study consisted of four parts: (1) curriculum design (the set of learning activities); (2) curriculum principles (assessing the design); (3) concepts and behaviors (assessing the content); and (4) context for implementation (the art of the practical). After examination of data from the five projects in these four areas, recommendations were made for improvements in each of these areas. (KC)
Sponsoring Agency: Department of Labor, Washington, DC.
ERIC Note: For related documents, see ED 224 901-903 and CE 036 049-053.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adolescents; Curriculum Development; Demonstration Programs; Employment Programs; Federal Programs; Learning Activities; Program Content; Program Implementation; Program Improvement; Secondary Education; Work Experience Programs; Youth Employment; Youth Employment and Demonstration Projects Act; Youthwork National Policy Study; Reports, Research